CULTIVATION OF BACILLUS SUBTILIS AND PSEUDOMONAS AERUGINOSA IN FISHERIES WASTE MEDIA AND ANTAGONISTIC TEST AGAINST Rhizoctonia sp. AND Fusarium sp - Ananta Kusuma Amanda; Andrea Ajeng Eirenne Kristianti; Libranika Dwi Miswati; Elis Nina Herliyana; Lutfi Hanafi; Rizki Nugraheni Amaliasuci (Journal of People, Forest and Environment, 2022)
Sustainable forest management as a complete ecosystem has problems that are often detrimental to the economy and ecology, one of which is disease. Some examples of pathogens that attack forestry plants are Rhizoctonia sp. and Fusarium sp. which cause leaf blight. An alternative to control it is using chitinolytic bacteria as biological agents which are cultured in fishery waste media. This research aims to (1) determine the appropriate formulation of fish waste as a growth medium for chitinolytic bacteria and (2) determine the ability of the antagonist test of chitinolytic bacteria in inhibiting the growth of pathogenic fungi causing leaf blight. The steps used consisted of (1) media preparation, (2) bacterial and fungal rejuvenation, (3) bacterial culturing in fishery waste media, (4) Bacillus subtilis and Pseudomonas aeruginosa antagonist tests against the fungus Rhizoctonia sp. and Fusarium sp., and (5) primary data analysis using OpenCFU and SAS applications. The result shows that the best fish waste formulation for growing chitinolytic bacteria was CR:KU:SI (2:1:1) with an average colony of 285 colonies for B. subtilis and 202 colonies for P. aeruginosa. The results of Anova analysis showed that the media formulation treatment has a significat effect on the growth of B. subtilis and P. aeruginosa bacterial colonies. The results of the in vitro antagonist test shows that the growth of Rhizoctonia sp could not be inhibited by the bacterium Pseudomonas aeruginosa. While the results of the antagonist test on Fusarium sp. shows if the P-value obtained is p>0,05, which means the data is not normally distributed or there is no effect of the application of B. subtilis and P. aeruginosa bacteria in inhibiting the growth rate of Fusarium sp.